Evidence for a functional interaction between the V1/V2 and C4 domains of human immunodeficiency virus type 1 envelope glycoprotein gp120. - Freed, E O (1994)
The domains of the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein that are required for envelope function have been partially characterized. Little is known, however, about the nature of the interactions between these domains. To identify regions of the HIV-1 envelope glycoprotein that are involved in interactions necessary for proper envelope function, we constructed a series of 14 envelope recombinants between the env genes of two HIV-1 isolates. The envelope chimeras were examined for their ability to induce syncytia, to be proteolytically processed, and to function during a spreading viral infection. Our results demonstrate that the exchange between the two isolates of the first and second hypervariable regions (V1/V2) of gp120 results in defects in envelope glycoprotein processing, syncytium formation, and infectivity. Long-term passage of cultures infected with virus bearing a V1/V2 chimeric envelope glycoprotein leads to the emergence of a revertant virus with replication characteristics comparable to those of the wild type. Analysis of the revertant indicated that an Ile-->Met change in the C4 region of gp120 (between hypervariable regions V4 and V5) is responsible for the revertant phenotype. This single amino acid change restores infectivity without significantly affecting gp160 processing, CD4 binding, or the levels of virion-associated gp120. While the Ile-->Met change in C4 greatly enhances the fusogenic potential of the V1/V2 chimeric envelope glycoprotein, it has a detrimental effect on syncytium formation when analyzed in the context of the wild-type envelope. These results suggest that an interaction required for proper envelope glycoprotein function occurs between the V1/V2 and C4 regions of gp120.